Synchronous and Asynchronous E-learning and Self-concept: The Case of Iranian EFL Learners - Ehsan Honarjou (Iranian Evolutionary Educational Psychology Journal, 2023)
The fact is that the process of English learning is complex and influenced by different factors. A factor which has been shown to have a key role in the process of language learning is technology. Accordingly, this study sought to investigate the effect of synchronous and asynchronous e-learning on EFL learners’ self-concept. In so doing, a quantitative quasi-experimental pre-test post-test design was utilized. The participants of the study included 60 male intermediate EFL learners studying English at a private language institute in Tehran, Iran. The sampling method of the study was convenience sampling because two intact intermediate classes were selected as the participants. The instruments used for the purpose of data collection were Quick Oxford Placement Test (QOPT) and Self-concept Questionnaire. Data analysis was conducted using descriptive and inferential statistics (i.e., paired samples t-tests and analysis of covariance (ANCOVA) test). The results of data analysis confirmed that asynchronous e-learning had a significant effect on self-concept of EFL learners. Moreover, the significant effect of synchronous e-learning on self-concept of EFL learners was proved by the results. In addition, it was found that no e-learning type was more effective than the other type of e-learning on EFL learners’ self-concept. The findings have some implications for EFL teachers, learners, and curriculum planners.